EASTERN ART - Radjabova Nargiza Ravshanovna (International Engineering Journal For Research & Development, 2021)
"Eastern culture" is a culture formed over the centuries. "Eastern culture" is based on the culture of different nations. This article discusses the Buddhist art, Chinese art, Indian art, Japanese and Korean art that shaped the Eastern culture.